A Framework for Optimization of Power Consumption in Mobile Computing Devices - Khadim, Faiza; Noreen, Iram; Muhammad, Abdul Hafeez (Mehran University research journal of engineering and technology, 2020)
Battery driven computing devices such as laptops and cellular phones have become a necessity in this era. Mobile applications help us in daily life activities and with the rise of Internet of Things (IoT) new opportunities are open up to automate different task. However, batteries have their own limitations such as weight, cost, and size. Multiple applications and background processes running in parallel easily drain phone’s battery within 24 hours consequently annoying users by limited battery capacity. Repeated charge, recharge cycles steadily diminish the full capacity of batteries resulting in the immense decreased performance of the device. Therefore, mobile devices and mobile applications are in great need of energy-aware modules. In this paper, a survey is performed to identify the needs of the mobile user in the context of energy consumption problem. The results of survey lead authors to propose a middle layer energy aware framework to address this issue. The proposed framework highly relies on the association between the operating system, application, and end user. The main objective of the proposed framework is to maintain an energy-aware capability to facilitate end user and mobile applications. The major components of the proposed framework are processing engine, application classifier, application resource management, system profiling, application modes, power estimator and power policy management. Proposed framework also offers a policy manager algorithm based on research community feedback and survey's results. Proposed framework emphasizes on energy efficient execution of mobile operations for end user and operating systems.